Effects of D-Chiro-Inositol on Glucose Metabolism in db/db Mice and the Associated Underlying Mechanisms - Chunxue Fan; Weishi Liang; Min Wei; Xiangbo Gou; Shuying Han; Jing Bai (Frontiers Media S.A., 2020)
In this study, we observed the effect of D-chiro-inositol (DCI) on glucose consumption in type 2 diabetic db/db mice, and investigated the relevant mechanism. We discovered that the stability of 24-h blood glucose under the nonfasting condition and decreased glucose tolerance were both alleviated after treatment with DCI. Moreover, the content of glycosylated protein and advanced glycation end products in the serum was reduced, the damage in the liver tissue was alleviated, and the synthesis of liver glycogen was significantly promoted. In addition, DCI increased the expression of insulin receptor substrate 2 (IRS2), phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT), glucose transporters 4 (GLUT4), and phospho-AKT (S473) protein. In contrast, DCI decreased the expression level of glycogen synthase kinase 3β (GSK3β) protein in liver tissue to various degrees, as shown by immunohistochemistry and western blotting. Furthermore, DCI increased the mRNA expression of IRS2, PI3K, AKT, and GLUT4, and reduced that of GSK3β in liver tissue, as demonstrated by polymerase chain reaction. Finally, DCI promoted glucose consumption in high glucose-stimulating HepG2 cells and increased the expression of IRS2 protein in HepG2 cells, as revealed by fluorescence staining and flow cytometry. Our results indicate that DCI can significantly improve glucose metabolism in diabetic mice and HepG2 cells. This effect may be associated with the upregulation of IRS2, PI3K, AKT, and GLUT4 and downregulation of GSK3β.